Genetic testing for prevention of severe drug‐induced skin rash - Alfirevic, Ana (Cochrane Database Syst Rev, 2019)
BACKGROUND: Drug‐induced skin reactions present with a range of clinical symptoms, from mild maculopapular skin rashes to potentially fatal blistering skin rashes — such as Stevens‐Johnson syndrome (SJS) or toxic epidermal necrolysis (TEN) — which may result in death. Milder reactions may be troublesome and lead to low drug compliance. The pathogenesis of these drug reactions is not yet fully understood; however, there is evidence that pretreatment genetic testing may help to predict and prevent these reactions in some cases. OBJECTIVES: To assess the effects of prospective pharmacogenetic screening to reduce drug‐associated skin reactions in a patient population. SEARCH METHODS: We searched the following databases up to July 2018: the Cochrane Skin Specialised Register, CENTRAL, MEDLINE, Embase and LILACS. We also searched five trials registers, and checked the reference lists of included studies and relevant reviews for further references to relevant randomised controlled trials (RCTs). SELECTION CRITERIA: We included RCTs of participants who had prospective pharmacogenetic screening to determine genetic variants associated with hypersensitivity reactions, compared with those who did not have prospective pharmacogenetic screening. We included participants in any setting, who were of any age, gender, and ethnicity, who had been prescribed drugs known to cause delayed type hypersensitivity reactions. DATA COLLECTION AND ANALYSIS: We used standard methodological procedures expected by Cochrane. To assess studies for inclusion, two review authors independently screened all of the titles and abstracts of publications identified by the searches. Because there was only one included study, many of the planned data analyses were not applicable to the review. We used GRADE to assess the quality of the included study. The review's primary outcomes were the incidence of severe skin rashes with systemic symptoms (such as fever and multiple organ involvement), and long‐term effects (such as scarring of eyelids or lung tissue). Secondary outcomes were hospitalisation for drug‐induced skin reactions, blistering skin reactions (such as SJS, hypersensitivity (HSS) syndrome), and death. MAIN RESULTS: One study, which was a randomised, double‐blind, controlled, multicentre trial, fulfilled our inclusion criteria. The trial included 1956 adult participants (74% men, with a mean age of 42 years) across 265 centres (medical centres, hospitals, outpatient clinics) in 19 countries around the world who were infected with HIV‐type 1 and who had not received abacavir previously. The participants, who had a clinical need for treatment with an antiretroviral‐drug regimen containing abacavir, were randomly assigned to undergo prospective human leukocyte antigen (HLA) Class I, locus B, allele 57:01 (HLA‐B*57:01) screening (prospective‐screening group) before this treatment, or to undergo a standard‐care approach of abacavir use without prospective HLA‐B*57:01 screening (control group). Participants who tested positive for HLA‐B*57:01 were not given abacavir; instead, they received antiretroviral therapy that did not include abacavir. The control group did have retrospective HLA‐B*57:01 pharmacogenetic testing. The trial duration was six months. Each participant was observed for six weeks. Assessments were performed at the time of study entry, at baseline (day one of abacavir treatment), and at weeks one, two and six. This study was funded by the manufacturer of abacavir, GlaxoSmithKline. The study did not assess any of our primary outcomes, and it measured none of our secondary outcomes in isolation. However, it did assess an outcome of (characteristically severe) hypersensitivity reaction which included (but was not limited to) our secondary outcomes of HSS and SJS/TEN. The study demonstrated that prospective HLA‐B*57:01 screening probably reduces the incidence of hypersensitivity reaction to abacavir. The incidence of clinically diagnosed HSS reaction to abacavir was lower in the screening arm (risk ratio (RR) 0.43, 95% confidence interval (CI) 0.28 to 0.67; 1650 participants; moderate‐quality evidence), as was immunologically confirmed HSS reaction (RR 0.02, 95% 0.00 to 0.37; 1644 participants; moderate‐quality evidence). A positive result from an epicutaneous patch test performed six to ten weeks after clinical diagnosis provided immunological confirmation. Overall, the study demonstrates a low risk of bias across five out of seven domains. There was a high risk of detection bias because hypersensitivity reactions were diagnosed by the principal investigator at the recruitment site without the use of predefined clinical criteria. Although there was also high risk of attrition bias due to excluding participants with incomplete follow‐up from analyses, the authors did undertake a series of sensitivity analyses based on the intention‐to‐treat population, which demonstrated consistent results with the primary analysis. We rated the study quality as moderate‐quality using GRADE criteria. AUTHORS' CONCLUSIONS: Prospective screening for HLA‐B*57:01 probably reduces severe hypersensitivity skin reactions to abacavir in patients positive for HIV‐type 1. However, these results are only based on one study, which was at high risk of attrition and detection bias. Our primary outcomes (incidence of severe skin rashes with systemic symptoms, and long‐term effects) were not assessed by the trial, and only one of the review’s secondary outcomes was measured (hypersensitivity reaction); thus, we found no evidence relating to hospitalisation, death, or long‐term conditions resulting from drug injury. We found no eligible evidence on genetic testing for severe drug‐induced skin rash in relation to different drugs and classes of drugs. Further clinical trials based on other drugs, and in different patient populations, would be useful for advising policy changes for improving the prevention of adverse skin reactions to drug treatments.